Preliminary study on the medical image collections of the University of the Philippines College of Medicine - Camacho, Albert Allan N. (2002)
Medical images are a vital information resource in the field of medicine. Its primary use is in educational, clinical and research reference. The University of the Philippines College of Medicine (UPCM) generates a great amount of this resource. How can these be managed in order to provide optimal acquisition, storage, and retrieval?